2014
DOI: 10.1039/c4cp02994a
|View full text |Cite
|
Sign up to set email alerts
|

Atomic domain magnetic nanoalloys: interplay between molecular structure and temperature dependent magnetic and dielectric properties in manganese doped tin clusters

Abstract: We present extensive temperature dependent (16-70 K) magnetic and electric molecular beam deflection measurements on neutral manganese doped tin clusters Mn/SnN (N = 9-18). Cluster geometries are identified by comparison of electric deflection profiles and quantum chemical data obtained from DFT calculations. Most clusters adopt endohedral cage structures and all clusters exhibit non-vanishing magnetic dipole moments. In the high temperature regime all species show exclusively high field seeking magnetic respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 76 publications
1
54
1
Order By: Relevance
“…The supersonic expansion vastly decreases the translational and rotational temperature of the clusters, but the influence on the vibrational temperature is small. 3,4,17,18 It has been demonstrated by the temperaturedependent superatomic response of Mn@Sn 12 that the vibrational temperature of the clusters is approximately equal to T nozzle with this setup if the clusters are sufficiently close to thermal equilibrium with the nozzle (before the supersonic expansion occurs). 3 The highly collimated molecular beam then passes a magnetic deflection unit with an inhomogeneous magnetic field (two-wire field analogue, 19 0−1.5 T, 0−335 T/ m).…”
Section: ■ Experimental Setupmentioning
confidence: 95%
See 3 more Smart Citations
“…The supersonic expansion vastly decreases the translational and rotational temperature of the clusters, but the influence on the vibrational temperature is small. 3,4,17,18 It has been demonstrated by the temperaturedependent superatomic response of Mn@Sn 12 that the vibrational temperature of the clusters is approximately equal to T nozzle with this setup if the clusters are sufficiently close to thermal equilibrium with the nozzle (before the supersonic expansion occurs). 3 The highly collimated molecular beam then passes a magnetic deflection unit with an inhomogeneous magnetic field (two-wire field analogue, 19 0−1.5 T, 0−335 T/ m).…”
Section: ■ Experimental Setupmentioning
confidence: 95%
“…3,4,17,18 It has been demonstrated by the temperaturedependent superatomic response of Mn@Sn 12 that the vibrational temperature of the clusters is approximately equal to T nozzle with this setup if the clusters are sufficiently close to thermal equilibrium with the nozzle (before the supersonic expansion occurs). 3 The highly collimated molecular beam then passes a magnetic deflection unit with an inhomogeneous magnetic field (two-wire field analogue, 19 0−1.5 T, 0−335 T/ m). The spatial distribution of the clusters in the molecular beam is then measured size selectively without and with applied magnetic field by a scanning slit and recording the cluster intensities by photo ionization time-of-flight mass spectrometry.…”
Section: ■ Experimental Setupmentioning
confidence: 95%
See 2 more Smart Citations
“…[24][25][26] There are some reports on the doped tin cluster. [27][28][29][30][31][32][33][34][35][36][37][38][39] An interesting example is icosahedral MnSn 12 cluster where Kumar and Kawazoe [27] showed that the doping of a Mn atom could increase the magnetic moment. The atom loss process was also enhanced when a tin atom was substituted by a lead atom in the homoatomic Sn þ 12 cluster.…”
Section: Introductionmentioning
confidence: 99%